2010
DOI: 10.1177/0956797610390385
|View full text |Cite
|
Sign up to set email alerts
|

Kin Affiliation Across the Ovulatory Cycle

Abstract: A commonplace observation in humans is that close genetic relatives tend to avoid one another as sexual partners. Despite the growing psychological research on how antierotic attitudes develop toward relatives, few studies have focused on actual behavior. One prediction, stemming from parental investment theory, is that women should be more vigilant of reproductioncompromising behaviors, such as inbreeding, during times of peak fertility than during times of low fertility. Indeed, females of other species avoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 26 publications
0
31
2
Order By: Relevance
“…Relatedly, women have been shown to decrease rape-related risky behaviors [15] and increase hand-grip strength in response to hypothetical rape scenarios [16] at high fertility compared to low (but see [17], for a discussion of the effectiveness of these behaviors). Women have also been shown to express greater sexual disgust sensitivity [18] and to selectively reduce affiliation with close male kin, but not close female kin [19] at high fertility relative to low. These patterns have been interpreted as reducing the possibility of reproductively costly scenarios such as inbreeding.…”
Section: Introductionmentioning
confidence: 99%
“…Relatedly, women have been shown to decrease rape-related risky behaviors [15] and increase hand-grip strength in response to hypothetical rape scenarios [16] at high fertility compared to low (but see [17], for a discussion of the effectiveness of these behaviors). Women have also been shown to express greater sexual disgust sensitivity [18] and to selectively reduce affiliation with close male kin, but not close female kin [19] at high fertility relative to low. These patterns have been interpreted as reducing the possibility of reproductively costly scenarios such as inbreeding.…”
Section: Introductionmentioning
confidence: 99%
“…By analyzing these naturalistically observed behaviors, we gain meaningful insight into the psychological state of users. For example, the automatic logs of phone communications (e.g., who, when, how long of calls and text messages) shed important information about the users [3]. Despite the privacy concern of smartphone data, many users still entirely or partially share their information through social media applications like Twitter, Facebook, LinkedIn, etc; Users voluntarily log into such Apps and share their thoughts, feelings, and daily activities.…”
Section: Two Approaches Of Using Smartphones In Researchmentioning
confidence: 99%
“…Behaviors aimed at reducing opportunities for inbreeding to occur are predicted to increase around ovulation (Lieberman et al, 2011) but have yet to be the focus of large-scale, rigorous tests. To date, the best evidence for ovulatory shifts in inbreeding-avoidance comes from Lieberman et al (2011).…”
mentioning
confidence: 99%
“…Behaviors aimed at reducing opportunities for inbreeding to occur are predicted to increase around ovulation (Lieberman et al, 2011) but have yet to be the focus of large-scale, rigorous tests. To date, the best evidence for ovulatory shifts in inbreeding-avoidance comes from Lieberman et al (2011). In a longitudinal study of 48 women's mobile phone records from one menstrual cycle, Lieberman et al reported that women called their fathers less frequently, and spoke to them for less time when they did call them, during the high-fertility phase of the menstrual cycle than when fertility was low.…”
mentioning
confidence: 99%
See 1 more Smart Citation